2012
DOI: 10.1001/archgenpsychiatry.2012.8
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Reactivity to a Single Inhalation of 35% Carbon Dioxide and Its Association With Later Symptoms of Posttraumatic Stress Disorder and Anxiety in Soldiers Deployed to Iraq

Abstract: Soldiers' emotional reactivity to a 35% CO(2) challenge may serve as a vulnerability factor for increasing soldiers' risk for PTSD and general anxiety/stress symptoms in response to war-zone stressors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(29 citation statements)
references
References 59 publications
1
28
0
Order By: Relevance
“…The goal of the present study was to replicate previously reported candidate gene associations with anxiety disorders using hypersensitivity to carbon dioxide (CO 2 ), a well-validated endophenotype of panic disorder (PD) (Coryell, 1997) and other anxiety disorders (Caldirola, Perna, Arancio, Bertani, & Bellodi, 1997; Telch, Rosenfield, & Pai, 2012). We examined the association between CO 2 hypersensitivity and 11 genes using both subjective and physiologic measures.…”
Section: Introductionmentioning
confidence: 89%
“…The goal of the present study was to replicate previously reported candidate gene associations with anxiety disorders using hypersensitivity to carbon dioxide (CO 2 ), a well-validated endophenotype of panic disorder (PD) (Coryell, 1997) and other anxiety disorders (Caldirola, Perna, Arancio, Bertani, & Bellodi, 1997; Telch, Rosenfield, & Pai, 2012). We examined the association between CO 2 hypersensitivity and 11 genes using both subjective and physiologic measures.…”
Section: Introductionmentioning
confidence: 89%
“…This question sets up a false dichotomy, as PTSD is rooted in both biological and psychological factors with regard to onset of symptoms, development of PTSD diagnosis, and maintenance of the disorder. Studies demonstrate that biological differences [36] and psychosocial differences [14,37] contribute to the risk for developing PTSD. Experimental research additionally provides evidence that both biological and psychological interventions delivered relatively soon after trauma exposure have the potential to mitigate or even prevent (in the case of psychotherapy for Acute Stress Disorder) the development of PTSD [38,39].…”
Section: Evidence-based Treatmentsmentioning
confidence: 99%
“…Higher risk for PTSD has also been associated with numerous pre-trauma variables, including female gender, disadvantaged social, intellectual, and educational status, history of trauma exposure prior to the index event, negative emotional attentional bias, anxiety sensitivity, genetic subtypes implicated in serotonin or cortisol regulation, as well as personal and family history of psychopathology [11,12,14,15,16,17]. PTSD risk factors related to peri-traumatic and post-traumatic variables include perceived life threat during the trauma, more intense negative emotions during or after the trauma (e.g., fear, helplessness, shame, guilt, and horror), dissociation during or after the trauma, lower levels of social support after the trauma, and generally more severe symptoms during the first week following the traumatic event [12,18].…”
Section: Introductionmentioning
confidence: 99%
“…The successive MHAT (MHAT-VI-OIF) suggested that symptoms of acute stress, the precursor to PTSD, and depression were greatest at approximately the midpoint of the deployment period (U.S. Department of the Army, Office of the Surgeon General, 2009). Similarly, a growth curve analysis of monthly changes in soldiers' PTSD and depressive symptoms during a deployment to Iraq found that symptoms were most severe roughly eight months into a 16-month deployment (i.e., roughly halfway through the deployment); however, symptoms declined to their baseline levels or lower by the end of the deployment (Telch et al, 2012). In contrast, there have been some longitudinal studies of symptoms following deployment.…”
Section: Symptoms Over a Deployment Cyclementioning
confidence: 99%